Survival and cardiovascular events after coarctation-repair in long-term follow-up (COAFU): Predictive value of clinical variables. (1st February 2017) - Bambul Heck, P.; Pabst von Ohain, J.; Kaemmerer, H.; Ewert, P.; Hager, A.
Abstract: Objective: Long-term sequelae and events after coarctation repair are well described. However, the predictive value of variables from clinical follow-up investigation for late events and survival has rarely been investigated. Methods: All patients who participated in the prospective cross-sectional COALA Study in 2000 with a structural clinical investigation including blood pressure measurement and symptom-limited exercise test were contacted for reevaluation of survival, current clinical status and major cardiovascular events. Results: Of 273 eligible patients, 209 were available for follow-up. Nine patients had died at a median age of 46 years (range 30–64 years), five of them due to cardiovascular complications. Late mortality after surgical intervention was 5.7% with a median age of 41 years (range 16–64 years). Twenty-five patients had a major cardiovascular event: 12 had procedures at the aortic valve or aortic arch, 8 had procedures for restenosis, 2 had endocarditis, 2 had a cerebrovascular insult and 1 an aortic dissection. The presence of bicuspid aortic valve ( p  = 0.009), brachial-ankle blood pressure gradient > 20 mmHg ( p  < 0.001) and reduced left ventricular function ( p  = 0.002) correlated with major cardiovascular events. Conclusion: Surgical correction of coarctation of the aorta shows fairly low mortality in the long-term follow-up. Late morbidities include recoarctation, but also the consequences of the hemodynamics produced by a congenital bicuspid aortic valve, presence of which is predictive for aortic valve procedures: however the predictive value of clinical variables is limited.